Well-Defined Iron Catalyst for Improved Hydrogenation of Carbon Dioxide and Bicarbonate - Ziebart, Carolin; Federsel, Christopher; Anbarasan, Pazhamalai; Jackstell, Ralf; Baumann, Wolfgang; Spannenberg, Anke; Beller, Matthias (Journal of the American Chemical Society, 2012)
The most efficient, stable, and easy-to-synthesize non-noble metal catalyst system for the reduction of CO2 and bicarbonates is presented. In the presence of the iron(II)-fluoro-tris(2-(diphenylphosphino)phenyl)phosphino]tetrafluoroborate complex 3, the hydrogenation of bicarbonates proceeds in good yields with high catalyst productivity and activity (TON > 7500, TOF > 750). High-pressure NMR studies of the hydrogenation of carbon dioxide demonstrate that the corresponding iron-hydridodihydrogen complex 4 is crucial in the catalytic cycle.